The effect of group size on individual behavior of bubble‐net feeding humpback whales in the southern Gulf of Maine. Issue 3 (10th January 2022) - Mastick, Natalie C.; Wiley, David; Cade, David E.; Ware, Colin; Parks, Susan E.; Friedlaender, Ari S.
Abstract: In many species, group foraging is a strategy used to increase the efficiency of individuals to find and exploit patchy prey. Humpback whales ( Megaptera novaeangliae ) are one of the few baleen whale species reported to use coordinated foraging strategies. One of these behaviors, bubble‐net feeding, has been observed in several populations, though the behaviors of individuals within these groups are largely unknown. This study used multisensor kinematic tag data from 26 whales foraging in the Southern Gulf of Maine to analyze individual bubble‐net feeding behaviors. Linear mixed effects models were used to test if there were differences in individual whales' dive behaviors across group size. The results indicate that individuals performed consistent bubble‐net feeding behaviors regardless of the size of their foraging group, except when using one specific foraging behavior, the upward spiral. Overall complexity of foraging dives, based on the three‐dimensional movements of the dive, decreased with increasing group size when group members used upward spirals. This may indicate that in larger groups, participants in coordinated feeding events need to move less and expend less energy to corral prey. This study provides new insights into the effects of group size on individual behavior and group coordination in humpback whales.